Tarascon pocket pharmacopoeia for nurses : 2012 classic for nurses - Rockstraw, Leland J.; Donnelly, Gloria F. (Burlington, MA : Jones & Bartlett Learning, 2012)
Contains a listing of drugs most commonly administered by bedside nurses. Nursing implications are included for each drug with tips on administration and patient education
Analgesics -- Anesthesia -- Antimicrobials -- Cardiovascular -- Dermatology -- Endocrine and metabolic - ENT -- Gastroenterology -- Hematology -- Herbal & alternative therapies -- Immunology -- Neurology -- OB/GYN -- Oncology -- Ophthalmology -- Psychiatry -- Pulmonary -- Toxicology -- Urology
Includes index
13
Keywords: Pharmaceutical Preparations -- administration & dosage -- Handbooks; Pharmaceutical Preparations -- administration & dosage -- Nurses' Instruction; Pharmacopoeias -- United States